Molecular signature of erythroblast enucleation in human embryonic stem cells. (13th May 2015) - Rouzbeh, Shaghayegh; Kobari, Ladan; Cambot, Marie; Mazurier, Christelle; Hebert, Nicolas; Faussat, Anne-Marie; Durand, Charles; Douay, Luc; Lapillonne, Hélène
Abstract: While enucleation is a critical step in the terminal differentiation of human red blood cells, the molecular mechanisms underlying this unique process remain unclear. To investigate erythroblast enucleation, we studied the erythroid differentiation of human embryonic stem cells (hESCs), which provide a unique model for deeper understanding of the development and differentiation of multiple cell types. First, using a two-step protocol, we demonstrated that terminal erythroid differentiation from hESCs is directly dependent on the age of the embryoid bodies. Second, by choosing hESCs in two extreme conditions of erythroid culture, we obtained an original differentiation model which allows one to study the mechanisms underlying the enucleation of erythroid cells by analyzing the gene and miRNA (miR) expression profiles of cells from these two culture conditions. Third, using an integrated analysis of mRNA and miR expression profiles, we identified five miRs potentially involved in erythroblast enucleation. Finally, by selective knockdown of these five miRs we found miR-30a to be a regulator of erythroblast enucleation in hESCs. Stem Cells   2015;33:2431–2441